Chemical activation of biochar-supported metal oxides for degradation of organic/inorganic and microbial contaminants - Urper, Osman; Taskin, Omer Suat; Eroğlu, Omer; Tonka, Mehdi; BAYDOGAN, Nilgun Do?an; Wang, Kaiying (Elsevier, 2023)
Biochar has excellent properties for removing organic and inorganic contaminants from wastewater and it can be used as a sorbent to degrade microbes from the environment owing to its large surface activity, porous properties, and high ion exchange capacity. Owing to their high reactivity, surface energy, and large surface area, metal oxides (MOs) have drawbacks such as passivation and aggregation, which decrease their good physicochemical properties. To overcome these drawbacks, biochar is a promising candidate to enhance the sorption capacity of MOs. Therefore, modified biochar with MOs can be used to maximize efficiency in removing contaminants from the environment. This chapter gives a short review on the fabrication, characterization, and modification of biochar MOs. The removal performance and antibacterial efficiency of biochar MOs are also discussed. © 2023 Elsevier Inc. All rights reserved.
Keywords: Biochar; Chemical adsorptivity; Efficient charge separation; Extended light absorption; Photocatalysis